2012
DOI: 10.5993/ajhb.36.6.10
|View full text |Cite
|
Sign up to set email alerts
|

Early Socioeconomic Disadvantage and Young Adult Sexual Health

Abstract: This study demonstrates how individual-, family-, and community-level characteristics and vulnerabilities contribute to young adult sexual risk and STI prevalence. Findings indicate specific individual characteristics and childhood experiences that should be specific targets of STI prevention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…In addition, Janssen, De Wit, Stroebe, and Van Griensven (2000) found young gay men from a lower socioeconomic status (SES) were at greater risk of HIV infection compared with peers from higher SES strata, due to less knowledge about HIV transmission and risk behaviors. Data from the National Longitudinal Study of Adolescent Health (Add Health) indicates adolescents from families and communities that are socioeconomically disadvantaged are at greater risk for sexually transmitted infections, less consistent use of condoms, more likely to have multiple sex partners and more likely to have experienced earlier sexual engagement (Wickrama, Merten, & Wickrama, 2012). Despite these findings, there is a need for more recent research that explores how SES and race/ethnicity are associated with sexual risk-taking behaviors in a new generation of YMSM.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Janssen, De Wit, Stroebe, and Van Griensven (2000) found young gay men from a lower socioeconomic status (SES) were at greater risk of HIV infection compared with peers from higher SES strata, due to less knowledge about HIV transmission and risk behaviors. Data from the National Longitudinal Study of Adolescent Health (Add Health) indicates adolescents from families and communities that are socioeconomically disadvantaged are at greater risk for sexually transmitted infections, less consistent use of condoms, more likely to have multiple sex partners and more likely to have experienced earlier sexual engagement (Wickrama, Merten, & Wickrama, 2012). Despite these findings, there is a need for more recent research that explores how SES and race/ethnicity are associated with sexual risk-taking behaviors in a new generation of YMSM.…”
Section: Introductionmentioning
confidence: 99%
“…These pathologies have been associated with increased engagement in high-risk sexual behaviors, 36,37 suggesting another mechanism by which SES-risk may increase STI acquisition. 38 This indirect path posits that adolescent adjustment (e.g., coping ability, mental health) may mediate the association between SES-related risk and later STI acquisition. 38 Wickrama et al identified a direct association between community-level disadvantage during childhood and STI prevalence in a nationally representative sample of young adults.…”
Section: Discussionmentioning
confidence: 99%
“…38 This indirect path posits that adolescent adjustment (e.g., coping ability, mental health) may mediate the association between SES-related risk and later STI acquisition. 38 Wickrama et al identified a direct association between community-level disadvantage during childhood and STI prevalence in a nationally representative sample of young adults. 38 Importantly, Wickrama’s study also found that adolescent adjustment difficulties and risky sexual practices only partially mediated the relationship between SES-related factors, suggesting that other, undetermined mechanisms may also mediate this relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 These theories have also been applied more generally (beyond crime) to neighborhood disorder and disadvantage. 22,23 The relationships between crime, fear of victimization, substance use, depressive symptoms, and sexual transmission risk-taking behavior are complex. Understanding the mechanism(s) underlying these relationships will be key to intervention development.…”
mentioning
confidence: 99%